Metal protection against atmospheric corrosion - Vladimir Vujičić (Vojnotehnički Glasnik, 1997)
The procedures of metal protection against atmospheric corrosion are described in this paper. The protection can be achieved by choice of metals, alloying, some structural measures, protective coatings and the treatment of corrosion environments.